Older people in Costa Rica: living conditions, gender and human rights - Espinoza Herrera, Rebeca (2026)
Introduction: Costa Rica is facing the phenomenon of demographic aging, which is leading to economic, social, and political changes, alongside challenges in health care, pensions, and caregiving, among others. Likewise, as a result of gender inequalities experienced and accumulated throughout the life course, old age is experienced differently depending on whether one is a woman or a man, which is why, when conducting studies on older persons, it is essential to disaggregate by sex the data produced about this population. In this way, information is available to address the specific needs of older people. Objective: The objective of this study is to analyze the living conditions of women and men aged 65 and over in Costa Rica, based on data on sociodemographic characteristics from the National Household Survey (ENAHO 2024). Method and Technique: This research employs data from the ENAHO 2024 survey, focusing on variables such as household headship, insurance status, poverty, and employment status, among others. Results: The research demonstrated significant gender-based differences among older adults in their access to employment, education, and health rights and in the use of Information and Communication Technologies, as well as inequalities in caregiving work, labor market participation, household maintenance, access to pensions, and unequal participation in household heads. [Continue reading in the article]